"They Love Us Because We Give Them Zakāt" : The Distribution of Wealth and the Making of Social Relations in Northern Nigeria - Abubakar, Dauda, (Islam in Africa ;, 2020)
In 'They Love Us Because We Give Them' Zakāt , Dauda Abubakar describes the practice of Zakāt in northern Nigeria. Those who practice this pillar of Islam annually deduct Zakāt from their wealth and distribute it to the poor and needy people within their vicinity, mostly their friends, relatives and neighbours. The practice of giving and receiving Zakāt in northern Nigeria often leads to the establishment of social relations between the rich and needy. Dauda Abubakar provides details of the social relationship in the people's interpersonal dealings with one another that often lead to power relations, high table relations etc. The needy reciprocate the Zakāt they collect in many ways, respecting and given high positions to the rich in society.